Impact of in vivo T-cell depletion in patients with myelodysplastic syndromes undergoing allogeneic hematopoietic stem cell transplant: a registry study from the Chronic Malignancies Working Party of the EBMT - Forcade, Edouard; Chevret, Sylvie; Finke, Jürgen; Ehninger, Gerhard; Ayuk, Francis; Beelen, Dietrich; Koster, Linda; Ganser, Arnold; Volin, Liisa; Sengeloev, Henrik; Michallet, Mauricette; Tischer, Johanna; et al. (Bone marrow transplantation, 2022)
While in vivo T-cell depletion (TCD) is widely used, its benefit in patients with MDS still remains a matter of debate. This study evaluates the impact of TCD on outcomes, and compares ATG and alemtuzumab, in patients with MDS. 1284 patients from the EBMT registry were included in this study with 470 patients in the no-TCD group and 814 in the TCD group (alemtuzumab N = 168; ATG N = 646). At 6 months, aGVHD III-IV cumulative incidences (CI) for no-TCD, ATG or alemtuzumab groups were 13% vs 14% vs 11% (ns), respectively. At 5 years, CI of chronic GVHD were 64% vs 52% vs 51% (p < 0.00017); and CI of relapse was 23% vs 25% vs 39% (p < 0.0001) for no TCD, ATG and alemtuzumab respectively; OS was 47% vs 46% vs 34% (p = 0.009) respectively; and GRFS was 21% vs 28% and 20% (p = 0.045) respectively. In multivariable analysis, ATG improved GRFS, and alemtuzumab decreased OS. Both ATG and alemtuzumab decreased risk of chronic GVHD, but the increased risk of relapse with alemtuzumab is associated with a poor GRFS and suggest to not use alemtuzumab in the setting of allo-SCT for high risk disease.
Keywords: recidiva; myelodysplastické syndromy; Myelodysplastic Syndromes; Neoplasms; Transplantation Conditioning; výsledek terapie; transplantace hematopoetických kmenových buněk; T-lymfocyty; homologní transplantace; Transplantation, Homologous; retrospektivní studie; lidé; nemoc štěpu proti hostiteli; T-Lymphocytes; Registries; registrace; Alemtuzumab; Treatment Outcome; Retrospective Studies; Humans; nádory; příprava pacienta k transplantaci; Hematopoietic Stem Cell Transplantation; Graft vs Host Disease; alemtuzumab; Recurrence